Correlating Structures to Electrochemiluminescence Efficiencies of Silole Compounds in Coreactant Systems. Issue 15 (9th August 2022) - Qin, Xiaoli; Yang, Liuqing; Wang, Xin; Patel, Darshil; Chu, Kenneth; Kelland, Lindsay; Adsetts, Jonathan Ralph; Zhang, Congyang; Workentin, Mark Steven; Pagenkopf, Brian L.; Ding, Zhifeng
Abstract: To develop efficient electrochemiluminescence (ECL) of activated silole chromophores, the relative ECL efficiencies of eight thiophene‐containing compounds are firstly studied in a coreactant pathway. The experimental results show that the extended π‐conjugated systems and donor groups of the silole emitters affect both the radical stability and emission efficiencies. It is found that the 1, 1‐di‐ tert ‐butyl‐2, 5‐bis[(2, 2′‐bithiophen)‐5‐yl]‐3, 4‐diphenylsilole (2c) compound with benzoyl peroxide (BPO) as a coreactant exhibits the highest relative ECL efficiencies among the studied systems due to its structural properties. Moreover, the absolute ECL efficiency of the potential pulsing/ECL experiment in the coreactant pathway is 6‐fold larger than that in the potentiodynamic experiment due to the short time interval for the radical species to meet and react. This work provides a guidance for structural modification of silole compounds to tune ECL performance. Abstract : Electroluminescence : To investigate the structure correlations to electroluminescence (ECL) performance, the relative ECL efficiencies of eight silole compounds have been determined in coreactant processes with benzoyl peroxide (BPO). The results reveal that the extended π‐conjugated systems and donor groups of the silole emitters affect both the radical stability and emission efficiencies. Spooling ECL spectroscopy provides more insights into the mechanisms of silole/BPO coreactant systems.